2001
DOI: 10.1177/00220345010800030701
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic Effects of Neurotrophins on a Periodontal Ligament Cell Line

Abstract: Nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and neurotrophin-3 (NT-3) are three representative neurotrophins responsible for the differentiation and survival of neurons, and their high-affinity receptors are tropomyosin-receptor-kinase (TRK)A, TRKB, and TRKC, respectively. In this study, we investigated the expression of neurotrophins in a mouse periodontal ligament cell line (MPL), by reverse transcription-polymerase chain-reaction (RT-PCR) and enzyme-linked immunoabsorbent assay (ELI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Although both BMP-1 and BMP-4 have been extensively studied and there is evidence to suggest that they have a role in hard tissue regeneration, 51,52 the relevance of brainderived neurotrophic factor (BDNF) in a mouse PDL cell line was described in a recent publication. 53 This growth factor belongs to a family of neutrotrophins and may be involved in neural tissue regeneration.…”
Section: Comparison Of Rt-pcr and Microarray Data (Mean Relative Ratimentioning
confidence: 99%
“…Although both BMP-1 and BMP-4 have been extensively studied and there is evidence to suggest that they have a role in hard tissue regeneration, 51,52 the relevance of brainderived neurotrophic factor (BDNF) in a mouse PDL cell line was described in a recent publication. 53 This growth factor belongs to a family of neutrotrophins and may be involved in neural tissue regeneration.…”
Section: Comparison Of Rt-pcr and Microarray Data (Mean Relative Ratimentioning
confidence: 99%
“…Concerning periodontal tissue regeneration, BDNF reportedly increased the synthesis of osteopontin, BMP-2, and collagen in human periodontal ligament (PDL) cells [10], strongly suggesting the existence of the Trk signaling pathway, which the receptor selectively binds to the BDNF [11]. It was further confirmed that a specific signaling pathway, TrkB-c-Raf-ERK1/2-Elk-1 was essential for the BDNF to induce mRNA expression of bone/cementum-related proteins [12] and also for the regulation of cementoblast survival [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms that could explain higher PDL regeneration potential with the use of BDNF have been previously speculated to be related to the increased synthesis of osteopontin, BMP‐2, and collagen in human periodontal ligament (PDL) cells, suggesting the existence of the Trk signaling pathway selectively binding to the BDNF …”
Section: Discussionmentioning
confidence: 99%